USING A SYSTEM APPROACH TO ENSURE BORDER SECURITY - Alagdaa, Ganbileg (International Journal of Innovative Technologies in Social Science, 2023)
If it is analyzing the border security from the point of view of national security is more extensive, but other side from the point of view of synergetic it will be requiring the participation of many researchers and professionals in this field, it is impossible to fully cover its content in one article. Therefore, in this article, the basic concepts of national security and border security, such as "national security", "national borders", "national border inviolability", "national border security", and national border protection, are analyzed from the cognitive point of view with a systemic approach. The purpose of this research was to answer the questions that required answers. From this research the results of the analysis are evidenced by the conclusions and practical findings based on the principles of constitutionalism and the definitions given by professionals from the perspective of knowledge. The security environment has changed and efforts have been made to identify the main issues that require further research and clarification on border security.